Nursing students attitudes across the suicidal behavior - Lappann Botti, Nadja Cristiane; Costa de Araújo, Leandro Martins; Costa, Elbert Eddy; de Almeida Machado, Jacqueline Simone (Investigación y Educación en Enfermería, 2015)
Objective. Examine the attitudes of nursing students with the suicidal behavior before and after a training course on the subject. Methodology. Performed quantitative, cross-sectional study, with 58 nursing students from a public university in Minas Gerais (Brazil) who participated in training on the theme. For data collection were used the Questionnaire of Attitudes Before Suicidal Behavior. The questionnaire was applied just before the start and the end of the training measuring attitudes toward suicidal behavior. Results. Were found statistically significant differences in negative feelings factors on the patient and perception of professional competence (p <0.05). The right factor to suicide was not significantly different among nursing students. Conclusion. The academic training may have influenced positively the desired changes regarding the attitudes of nursing students across the suicidal behavior. How to cite this article: Botti NCL, Araújo LMC, Costa EE, Machado JSA. Nursing students attitudes across the suicidal behavior. Invest Educ Enferm. 2015; 33(2):